y+.7-4.5=2.3(y-3)

Simple and best practice solution for y+.7-4.5=2.3(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+.7-4.5=2.3(y-3) equation:


Simplifying
y + 0.7 + -4.5 = 2.3(y + -3)

Reorder the terms:
0.7 + -4.5 + y = 2.3(y + -3)

Combine like terms: 0.7 + -4.5 = -3.8
-3.8 + y = 2.3(y + -3)

Reorder the terms:
-3.8 + y = 2.3(-3 + y)
-3.8 + y = (-3 * 2.3 + y * 2.3)
-3.8 + y = (-6.9 + 2.3y)

Solving
-3.8 + y = -6.9 + 2.3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2.3y' to each side of the equation.
-3.8 + y + -2.3y = -6.9 + 2.3y + -2.3y

Combine like terms: y + -2.3y = -1.3y
-3.8 + -1.3y = -6.9 + 2.3y + -2.3y

Combine like terms: 2.3y + -2.3y = 0.0
-3.8 + -1.3y = -6.9 + 0.0
-3.8 + -1.3y = -6.9

Add '3.8' to each side of the equation.
-3.8 + 3.8 + -1.3y = -6.9 + 3.8

Combine like terms: -3.8 + 3.8 = 0.0
0.0 + -1.3y = -6.9 + 3.8
-1.3y = -6.9 + 3.8

Combine like terms: -6.9 + 3.8 = -3.1
-1.3y = -3.1

Divide each side by '-1.3'.
y = 2.384615385

Simplifying
y = 2.384615385

See similar equations:

| 10-(1/3)x | | 5x+6=24+2x | | x-0.5x-0.5x-0.25x=12 | | 5(a-4)=35 | | (13x+9)=(5x+9) | | -6x-5=-9 | | (5x+5)=(115) | | x-6.0=26.0 | | 7y+9=8y+1 | | 2x^4-5x=2 | | 5x+29.0=54.0 | | 2y-71.0=25.0 | | 1/3x^3-4x-11/3 | | 4w+5=3w+9 | | loge(42)=2x+1 | | 6y=-2-x | | (x*40)+(1.5x*5)=576 | | 69*200000/X=17.92 | | 5/7m35 | | -8(s+2)=28 | | x*40+1.5*x*5=30000 | | 9w=10w-4 | | 2y-63.0=10.0 | | 2b-7/3=3/3 | | x-2.0=27.0 | | -8x+6-12=-30 | | 6x+21=x+7 | | 12+4x-x=x+28 | | 5x+28.0=58.0 | | 2b-31/3=11/3 | | (x+5)=(3x-2) | | 11/30x360 |

Equations solver categories